FEASIBILITY ANALYSIS OF RAM FARMING IN SUBANG REGENCY, WEST JAVA, INDONESIA - Ferdi Fathurohman; Nurul Mukminah; Fitri Suciati; Rita Purwasih (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
This study aimed to investigate the feasibility of ram farming and the factors that influence its ownership in Subang Regency, West Jawa, Indonesia. As primary data, sampling was carried out by purposive sampling on 60 breeders in Padamulya and Wanasari Village in Cipunagara District and Sumur Barang Village in Cibogo District where those locations were determined by Location Quotient (LQ). Business financial feasibility was deliberated based on Net Present Value (NPV), Total Revenue Cost Ratio (R/C), Benefit Cost Ratio (B/C), Internal Rate of Return (IRR), Payback Period (PP), and Break Event Point (BEP). Secondary data were obtained from Statistics Indonesia and the Livestock and Animal Health Services in Subang Region. The results showed that financially ram farming with a period of 5 years and a discount factor of 12%/year was feasible. Moreover, the number of ram ownership was significantly influenced by agricultural land (P<0.01), business experience, and the number of laborers (P<0.1). Thus, ram farming in Subang Regency has development potential.